Sistema de costos por órdenes de producción para la asociación agropecuaria Mariscal Sucre ubicada en el cantón Otavalo, provincia Imbabura. - Coyago Chimarro, Mery Elizabeth (2019)
There are currently several organizations involved in the development of products whose prices are inappropriate for their production. However, the lack of professional and technical support in the accounting field causes that these organizations are not able to maintain in the market because they can not achieve profitability that will allow them to continue their business, generating inefficient use of existing resources. The present integrating project consists of the development of a cost system that adapts to the production needs of the Agricultural Association Mariscal Sucre, avoiding waste of material and technological resources as well as unnecessary efforts that might raise production costs, through descriptive research that will allow the detailed description of the process involved in making jams, besides investigative techniques as interviews, observation sheets and direct investigations with those involved, which allowed the collection of useful and necessary data. By analyzing the information obtained, the need to design the system determined, the same one that will allow knowing with accuracy the three elements of the cost that incur in the production as there are: Raw material, labor, and indirect manufacturing costs. Concerning the sale price that the association established empirically can denote the economic loss that has generated during time caused by production manners. The designed cost system is an information tool of vital importance because it allows adding the cost elements through the use of a cost sheet defining a profit margin, to determine the unit cost of each flavor of jam. It was possible to avoid loss by calculating the contribution margin made in conjunction with the break-even point by identifying how many units must produce in order not to win or lose with the price thrown by the cost system. This way we could encourage the use of accounting tools that allow Associations such as this one to optimize their resources to improve the financial management of their businesses in order to obtain a more significant benefit for their members.